Visual performance and motorcycle safety-related impacts of various high beam headlight intensities - Prasetijo, Joewono; Mohd Jawi, Z.; Johari, M. H.; Mustafa, M. A.; Zhang, G.; Ramli, M. F.; Zulkifli, A. F. H.; Hamid, A. (Society of Automotive Engineers Malaysia, 2020)
In Malaysia, the three main types of motorcycle accidents include collision with passenger cars, collision with other motorcycles and single-motorcycle accidents. An accident may occur due to the lack of road design consistency and visibility where most drivers make more errors in the absence of geometric features. One of the most important barriers to the more frequent use of high beam headlight is the length of visibility of the headlight beam in relation to the stopping distance of a vehicle. Furthermore, it is crucial to evaluate the current limits on the luminous intensity of high beam headlights that is considered visible for a driver to come to a stop. Therefore, this first stage study summarizes and investigates the stopping sight distances, braking distances that allow for the evaluation of the vehicle's performance to increase the capability of both the driver and vehicle with regard to safety. A total of ten experiments were carried out with a passenger car, the Perodua Myvi, on a road within a local university. The results found that Stopping Sight Distance (SSD) could be used to determine the SSD graph by considering the velocity (v0), driver’s perception reaction time (tR), coefficient of breaking friction (fT), gravitational constant (g), deceleration rate (a) and roadway grade (G). The study also concludes that SSD could be used to determine the SSD graph by considering the velocity (v0), driver’s perception reaction time (tR), coefficient of breaking friction (fT), gravitational constant (g), deceleration rate (a) and roadway grade (G). Ultimately, the study also indicates that the time to switch to hi-beam (Automatic High Beam – AHB) is at SSD distance (meter or second).